Pengaruh Tingkat Pendidikan, Skala Usaha Dan Pengalaman Usaha Terhadap Penggunaan Informasi Akuntansi - Indah Hesti Mubarokah; Ceacilia Srimindarti (Universitas Pendidikan Ganesha, 2022)
Abstract This study aims to examine and analyze the effect of education level, business scale and business experience on the use of accounting information. The population in this study were all MSME actors registered at the Cooperatives and MSMEs Service in Semarang City. The sampling method in this study uses convenience sampling. The sample in this study amounted to 77 respondents of MSME actors registered at the Cooperatives and MSMEs Service in Semarang City. The results of this study explain that education level, business scale and business experience have a significant positive effect on the use of accounting information. Keywords: Use of Accounting Information, Education Level